Sosialisasi Pentingnya Keamanan Digital di Era Revolusi Industri 4.0 di Desa Gajah Mati Bengkulu Tengah - Toibah Umi Kalsum; Jhoanne Fredricka; Liza Yulianti; Indra Kanedi; Aji Sukmo (Jurnal Dehasen Untuk Negeri, 2022)
This community service activity in the form of socializing the importance of digital security in the era of the industrial revolution 4.0 aims to help the residents of Gajah Mati village, Central Bengkulu, in getting information about technological advances and how to maintain digital security. The subjects in this service activity were the Head of Gajah Mati Village and his apparatus and all residents of Gajah Mati Village, Central Bengkulu. This socialization process is carried out by providing information about security and prevention in the face of technological advances and fraudulent fraud in cyberspace. The result of this community service activity is that it can help villagers know about technological advances, how to deal with various kinds of online fraud so that they can slightly reduce victims of cybercrime. The conclusion of this community service activity in Gajah Mati Village, Central Bengkulu, is that it can provide information about technological advances, use technology, one of which is the use of Android smartphones, and help the community in dealing with fraud - fraud in cyberspace so that citizens can think smart if face the problem of fraud - fraud in cyberspace because they have received information and how to overcome it through this socialization. So the victims of crimes in cyberspace are slightly reduced.